X-linked deletion of Crossfirre, Firre, and Dxz4 in vivo uncovers diverse phenotypes and combinatorial effects on autosomes - Tim P. Hasenbein; Sarah Hoelzl; Zachary D. Smith; Chiara Gerhardinger; Marion O. C. Gonner; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Nathalia R. V. Dragano; Patricia da Silva-Buttkus; Lillian Garrett; et al. (Nature Communications)
Abstract The lncRNA Crossfirre was identified as an imprinted X-linked gene, and is transcribed antisense to the trans-acting lncRNA Firre. The Firre locus forms an inactive-X-specific interaction with Dxz4, both loci providing the platform for the largest conserved chromatin structures. Here, we characterize the epigenetic profile of these loci, revealing them as the most female-specific accessible regions genome-wide. To address their in vivo role, we perform one of the largest X-linked knockout studies by deleting Crossfirre, Firre, and Dxz4 individually and in combination. Despite their distinct epigenetic features observed on the X chromosome, our allele-specific analysis uncovers these loci as dispensable for imprinted and random X chromosome inactivation. However, we provide evidence that Crossfirre affects autosomal gene regulation but only in combination with Firre. To shed light on the functional role of these sex-specific loci, we perform an extensive standardized phenotyping pipeline and uncover diverse knockout and sex-specific phenotypes. Collectively, our study provides the foundation for exploring the intricate interplay of conserved X-linked loci in vivo.